Dakwah Di Tengah Pandemi (Studi Terhadap Respons Dai Di Media Sosial) - Hidayati, Diajeng Laily; Fahlevi, Reza (IAIN Samarinda, 2020)
The Covid-19 (Corona Virus Disease-19) outbreak has managed to change the patterns of social life on society, including the change regarding the way Da’wa is performed; from conventional direct Da’wa to mediated Da’wa through internet. This article aims at describing responses of the Da’is (proselytizers) in social media pertaining to the spread of the Covid-19. This article applied qualitative method to analyse Da’wa contents related to Covid-19 on social media. Data were collected through observation and documentation. Findings show that there are at least three types of responses from the Da’is; cognitive, affective, and behavioural responses. Cognitive response is manifested in the form of delivering information regarding Covid-19 from the general and medical perspective such as promoting frequent hand-washing, maintaining good hygiene, obeying the government measurements, maintaining healthy level of gratitude and praying to God to be saved from the outbreak. Affective response is manifested in the form of promoting empathy, positive thinking, and avoiding panic. Behavioural response is manifested in the form of giving real-life example such as performing online congregation (pengajian online), wearing face mask, applying appropriate disinfection, and helping those heavily affected by the outbreak.Keywords: Covid-19, Dai, responses, and social media.